Conductive and heat-conductive graphene paste and preparation method thereof

CN123033804APending Publication Date: 2026-11-03ZHONGKE SHENGHONG (DALIAN) NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611530827.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-30
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

[0003]现有石墨烯浆料通常采用单一规格的石墨烯或金属粉体,所构建的导电通路在低电阻率与高连通性之间难以兼顾,限制了浆料导电性能的进一步提升,同时,单一填料体系形成的导热网络连续性不足,浆料的导热性能也受到制约

Benefits of technology

1、本发明中,A组分材料以大片径石墨烯与片状银粉、镀银铜粉配合,构建以石墨烯为导电骨架、金属粉体为低电阻节点的导电主干网络,有效降低了浆料的电阻率,B组分材料以小片径石墨烯、多壁碳纳米管和超导炭黑配合,形成高连通性的毛细导电网络,填补主干网络之间的空隙,两套导电网络互穿互补,使浆料同时具备低电阻率和高连通性,解决了现有技术中单一填料体系导电通路结构单一、低电阻率与高连通性难以兼顾的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123033804A_ABST
    Figure CN123033804A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of conductive paste, in particular to a graphene paste for conducting electricity and heat and a preparation method thereof, which comprises component A material, component B material, component C material and base raw material.In the present application, the component A material is composed of large flake diameter graphene, flaky silver powder and silver-plated copper powder, which builds a conductive backbone network with graphene as the conductive framework and metal powder as the low resistance node, effectively reducing the resistivity of the paste.The component B material is composed of small flake diameter graphene, multi-walled carbon nanotubes and superconducting carbon black, which forms a high-connectivity capillary conductive network to fill the gaps between the backbone network.The two sets of conductive networks are interpenetrated and complementary, so that the paste has both low resistivity and high connectivity, solving the problem in the prior art that the single filler system has a single conductive path structure and it is difficult to balance low resistivity and high connectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of conductive paste technology, specifically to a graphene paste for conductive and thermal conduction and its preparation method. Background Technology

[0002] Graphene slurry is a slurry-like dispersion system formed by dispersing graphene in a liquid medium. Graphene has excellent electron mobility and thermal conductivity, so graphene slurry has good electrical and thermal conductivity and has application value in electronic devices, heat dissipation management, conductive coatings and electromagnetic shielding.

[0003] Existing graphene slurries typically use graphene or metal powder of a single specification. The resulting conductive pathways struggle to balance low resistivity and high connectivity, limiting further improvements in the slurry's conductivity. Furthermore, the lack of continuity in the thermally conductive network formed by a single filler system also restricts the slurry's thermal conductivity. Therefore, this invention provides a conductive and thermally conductive graphene slurry and its preparation method. Summary of the Invention

[0004] The purpose of this invention is to provide a graphene slurry for electrical and thermal conductivity and its preparation method. The graphene slurry for electrical and thermal conductivity prepared by this invention not only has good electrical conductivity but also good thermal conductivity.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A graphene slurry for electrical and thermal conductivity includes component A, component B, component C, and base raw materials; The raw materials for component A include graphene, silver powder, silver-plated copper powder, and ionic liquid; The graphene sheets in component A have a diameter of 10-30 μm and ≤5 layers; the silver powder is flake-shaped silver powder with a diameter-to-thickness ratio of 30:1 and a particle size of 5-10 μm; and the silver-plated copper powder has a particle size of 3-5 μm. The raw materials for component B include graphene, multi-walled carbon nanotubes, carbon black, and ionic liquids. The graphene sheets in component B have a diameter of 1-3 μm and ≤3 layers, the multi-walled carbon nanotubes have a diameter of 10-20 nm and a length of 10-30 μm, and the carbon black is superconducting carbon black with a particle size of 30-50 nm. The C component material is prepared by mixing the A component material and the B component material, wherein the mass ratio of the total mass of the raw materials of the A component material to the total mass of the raw materials of the B component material is 1.7-2.1:1; The basic raw materials include ionic liquids, epoxy resins, diluents, curing agents, coupling agents, and dispersants. The epoxy resin used in the basic raw materials is E44 type epoxy resin, the diluent is epoxy diluent AGE, the curing agent is phthalic anhydride, the coupling agent is KH560, and the dispersant is PVP K-30.

[0006] Preferably, the A component material is prepared by the following method: the ionic liquid is preheated to 55-60°C, graphene is added to the preheated ionic liquid, and ultrasonic treatment is performed for 30-40 minutes. Then, the liquid is cooled to 4-10°C in an ice-water bath, and silver powder and silver-plated copper powder are added in sequence. The liquid is then ultrasonically dispersed under ice-water bath conditions for 30-40 minutes to obtain the A component material.

[0007] Preferably, the B component material is prepared by the following method: the ionic liquid is preheated to 55-60°C, graphene, multi-walled carbon nanotubes and carbon black are added sequentially to the preheated ionic liquid, ultrasonic treatment is performed for 50-60 minutes, the resulting product is transferred to a high-pressure homogenizer, set to 800-1200 bar, cyclically 5 times, and the jacket is water-cooled to control the temperature at ≤35°C to obtain the B component material.

[0008] Preferably, the C component material is prepared by the following method: adding the B component material to the A component material while maintaining a stirring state of 1000-2000 rpm during the addition process, after the addition is completed, the resulting product is transferred to a high-pressure homogenizer and circulated 3 times at 500-600 bar. Adding an additive of 20% of the mass of the B component material to the resulting product, and stirring in a mixer at 800-1200 rpm for 20-40 minutes, the C component material is obtained.

[0009] Preferably, the additive is prepared by the following method: nitrogen-doped graphene powder is added to deionized water and ultrasonically treated for 10-15 min to obtain a dispersion. Aniline is added to the dispersion, and the mixture is magnetically stirred at 200-300 rpm for 10-15 min. Then, carboxylated short-cut multi-walled carbon nanotubes are added and ultrasonically dispersed for 5-10 min. Ammonium persulfate solution is added dropwise while maintaining stirring. After the addition is complete, stirring is continued for 30 min. 1 mol / L hydrochloric acid is added to adjust the pH to 2-3, and stirring is continued for 5-10 min. The resulting product is centrifuged to obtain a solid. The solid is washed 4-6 times with deionized water and then vacuum dried at 60-80℃ for 4-5 h. The solid is then ground and sieved through a 300-mesh sieve to obtain the additive.

[0010] Preferably, the mass ratio of each raw material in component A is 10:7-8:17-18:6-7.

[0011] Preferably, the mass ratio of each raw material in component B is 10:6-7:4-5:1.5-2.

[0012] Preferably, the mass ratio of each raw material in the basic raw material is 10:18:1.5-1.8:4-4.5:0.2-0.3:0.6-0.8, and the mass ratio of the C component material to the basic raw material is 1.8-2.1:1.

[0013] Preferably, the nitrogen-doped graphene powder has a nitrogen content of 3-5 at%, ≤4 layers, and a sheet diameter of 20 μm. The mass ratio of the nitrogen-doped graphene powder to deionized water is 1:50. The mass of aniline is 4-6% of the mass of the dispersion. The mass of carboxylated short-cut multi-walled carbon nanotubes is 0.2-0.3% of the mass of the dispersion. The mass of ammonium persulfate solution is 3-5% of the mass of the dispersion. The concentration of the ammonium persulfate solution is 1 mol / L.

[0014] A method for preparing a graphene slurry for conductive and thermally conductive applications includes the following steps: epoxy resin, diluent, and coupling agent are added to a mixer and stirred at 100-200 rpm for 10-20 minutes. Then, component C, ionic liquid, and dispersant are added, and the mixture is transferred to a high-pressure homogenizer and circulated 3 times at 500-600 bar with jacket water cooling and temperature control ≤40℃. After that, the mixture is transferred to a vacuum mixing vessel and stirred at -0.095 MPa, 55-60℃, and 100-200 rpm for 60-90 minutes. Then, a curing agent is added and mixed evenly, and the mixture is stirred at 2000 rpm for 5 minutes to obtain the graphene slurry for conductive and thermally conductive applications.

[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, component A is composed of large-diameter graphene combined with sheet-like silver powder and silver-plated copper powder to construct a conductive backbone network with graphene as the conductive framework and metal powder as low-resistance nodes, effectively reducing the resistivity of the slurry. Component B is composed of small-diameter graphene, multi-walled carbon nanotubes and superconducting carbon black to form a highly interconnected capillary conductive network, filling the gaps between the backbone networks. The two sets of conductive networks interpenetrate and complement each other, enabling the slurry to simultaneously possess low resistivity and high connectivity, solving the problem in the prior art where the conductive pathway structure of a single filler system is simple and it is difficult to achieve both low resistivity and high connectivity.

[0016] 2. In this invention, both component A and component B use graphene as the core functional component. The excellent thermal conductivity of graphene itself forms a continuous heat conduction channel in the two sets of conductive networks. The large-diameter graphene in component A provides a long-range heat conduction path, while the small-diameter graphene and multi-walled carbon nanotubes in component B fill the short-range heat conduction gaps. After the two interpenetrate, they form a heat conduction network covering the entire slurry, so that the slurry has good thermal conductivity while obtaining excellent electrical conductivity, which meets the requirements of electronic device heat dissipation management for conductive and thermally conductive integrated slurry.

[0017] 3. In this invention, the additive is prepared by polymerization of nitrogen-doped graphene powder, aniline, and carboxylated short-cut multi-walled carbon nanotubes. The conductive polymer formed by aniline polymerization, after being combined with nitrogen-doped graphene and carboxylated carbon nanotubes, serves as an auxiliary conductive phase, which can further fill the gaps between component A and component B, thereby improving the overall conductivity of the slurry. At the same time, the presence of polar groups on the surface of carboxylated carbon nanotubes and conductive polymers helps to improve the dispersion state of the additive in the slurry, reduce the agglomeration between carbon materials, and improve the storage stability of the slurry. Attached Figure Description

[0018] Figure 1 The present invention provides a flowchart of a graphene slurry for conductive and thermally conductive applications and its preparation method. Detailed Implementation

[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0020] It should be noted that the raw materials used in the following embodiments are all commercially available.

[0021] Example 1

[0022] Preparation of component A material: The ionic liquid was preheated to 55°C, graphene was added, and ultrasonic treatment was performed for 30 min. Then, the liquid was cooled to 4°C in an ice-water bath, and flake silver powder and silver-plated copper powder were added in sequence. The mixture was ultrasonically dispersed for 30 min under ice-water bath conditions to obtain component A material. The mass ratio of graphene, silver powder, silver-plated copper powder, and ionic liquid is 10:7:17:6. The graphene sheet diameter is 10μm and the number of layers is ≤5. The aspect ratio of the sheet-like silver powder is 30:1 and the particle size is 5μm. The particle size of the silver-plated copper powder is 3μm.

[0023] Preparation of component B materials: The ionic liquid was preheated to 55°C, and graphene, multi-walled carbon nanotubes and superconducting carbon black were added in sequence. The mixture was ultrasonically treated for 50 minutes. The resulting product was transferred to a high-pressure homogenizer, set to 800 bar, and circulated 5 times. The jacket was water-cooled and the temperature was controlled to ≤35°C to obtain the B component material. The mass ratio of graphene, multi-walled carbon nanotubes, superconducting carbon black, and ionic liquid is 10:6:4:1.5. The graphene sheet diameter is 1μm and the number of layers is ≤3. The multi-walled carbon nanotubes have a diameter of 10nm and a length of 10μm. The superconducting carbon black has a particle size of 30nm.

[0024] Preparation of component C materials: Add component B to component A (the mass ratio of the total mass of raw materials in component A to the total mass of raw materials in component B is 2:1). During the addition process, maintain a stirring state of 1000 rpm. After the addition is completed, transfer to a high-pressure homogenizer and cycle 3 times at 500 bar. Add 20% of the mass of component B to the resulting product as an additive and stir in a mixer at 800 rpm for 20 minutes to obtain component C.

[0025] Additive preparation: Nitrogen-doped graphene powder was added to deionized water and ultrasonically treated for 10 min to obtain a dispersion. Aniline was added to the dispersion at 4% by weight, and the mixture was magnetically stirred at 200 rpm for 10 min. Then, carboxylated short-cut multi-walled carbon nanotubes were added at 0.2% by weight, and the mixture was ultrasonically dispersed for 5 min. A 3% by weight ammonium persulfate solution was added dropwise while stirring. After the addition was complete, stirring was continued for 30 min. 1 mol / L hydrochloric acid was added to adjust the pH to 2, and stirring was continued for 5 min. The solid was obtained by centrifugation, washed four times with deionized water, vacuum dried at 60℃ for 4 h, ground, and sieved through a 300-mesh sieve to obtain the additive. The nitrogen-doped graphene powder has a nitrogen content of 3 at%, a nitrogen-doped graphene powder to deionized water mass ratio of 1:50, ≤4 layers, a sheet diameter of 20 μm, and an ammonium persulfate solution concentration of 1 mol / L.

[0026] Basic raw material preparation: Ionic liquid, E44 type epoxy resin, epoxy diluent AGE, phthalic anhydride, KH560, and PVP K-30 are prepared in a mass ratio of 10:18:1.5:4:0.2:0.6.

[0027] Graphene slurry preparation: Epoxy resin, diluent, and coupling agent were added to a mixer and stirred at 100 rpm for 10 minutes. Then, component C, ionic liquid, and dispersant were added and transferred to a high-pressure homogenizer. The mixture was circulated at 500 bar for 3 cycles, with jacket water cooling and temperature control ≤40℃. After that, it was transferred to a vacuum mixer and stirred at -0.095 MPa, 55℃, and 100 rpm for 60 minutes. Then, curing agent was added and mixed thoroughly. The mixture was then stirred at 2000 rpm for 5 minutes to obtain a graphene slurry for electrical and thermal conductivity. After coating, it was pre-cured at 80℃ for 1 hour and then cured at 130℃ for 2 hours. The mass ratio of component C to the base raw material was 1.8-2.1:1.

[0028] Example 2

[0029] Preparation of component A material: The ionic liquid was preheated to 58°C, graphene was added, and ultrasonic treatment was performed for 35 min. Then, the temperature was lowered to 7°C in an ice-water bath, and flake silver powder and silver-plated copper powder were added in sequence. The mixture was ultrasonically dispersed for 35 min under ice-water bath conditions to obtain component A material. The mass ratio of graphene, silver powder, silver-plated copper powder, and ionic liquid is 10:7.5:17.5:6.5. The graphene sheet diameter is 20μm and the number of layers is ≤5. The aspect ratio of the sheet-like silver powder is 30:1 and the particle size is 8μm. The silver-plated copper powder has a particle size of 4μm.

[0030] Preparation of component B materials: The ionic liquid was preheated to 58°C, and graphene, multi-walled carbon nanotubes and superconducting carbon black were added in sequence. The mixture was ultrasonically treated for 55 min, and the resulting product was transferred to a high-pressure homogenizer. The homogenizer was set to 1000 bar and cyclically run 5 times. The jacket was water-cooled and the temperature was controlled to ≤35°C to obtain the B component material. The mass ratio of graphene, multi-walled carbon nanotubes, superconducting carbon black, and ionic liquid is 10:6.5:4.5:1.8. The graphene sheet diameter is 2μm and the number of layers is ≤3. The multi-walled carbon nanotube diameter is 15nm and the length is 20μm. The superconducting carbon black particle size is 40nm.

[0031] Preparation of component C materials: Add component B to component A while stirring at 1500 rpm. After addition, transfer to a high-pressure homogenizer and cycle at 550 bar for 3 times. Add 20% of the mass of component B as an additive to the product and stir at 1000 rpm for 30 minutes in a mixer to obtain component C.

[0032] Additive preparation: Nitrogen-doped graphene powder was added to deionized water and ultrasonically treated for 12 min to obtain a dispersion. 5% (by weight) aniline was added to the dispersion, and the mixture was magnetically stirred at 250 rpm for 12 min. Then, 0.25% (by weight) carboxylated short-cut multi-walled carbon nanotubes were added, and the mixture was ultrasonically dispersed for 8 min. 4% (by weight) ammonium persulfate solution was added dropwise while maintaining stirring. After the addition was complete, stirring continued for 30 min. 1 mol / L hydrochloric acid was added to adjust the pH to 2.5, and stirring continued for 8 min. The mixture was centrifuged to obtain a solid, washed five times with deionized water, vacuum dried at 70℃ for 4.5 h, ground, and sieved through a 300-mesh sieve to obtain the additive. The nitrogen-doped graphene powder has a nitrogen content of 4 at%, a layer count of ≤4, a sheet diameter of 20 μm, a nitrogen-doped graphene powder to deionized water mass ratio of 1:50, and an ammonium persulfate solution concentration of 1 mol / L.

[0033] Basic raw material preparation: Prepare materials in the following mass ratios: ionic liquid, E44 type epoxy resin, epoxy diluent AGE, phthalic anhydride, KH560, and PVP K-30.

[0034] Graphene slurry preparation: Epoxy resin, diluent, and coupling agent were added to a mixer and stirred at 150 rpm for 15 min. Then, component C, ionic liquid, and dispersant were added, and the mixture was transferred to a high-pressure homogenizer and circulated at 550 bar for 3 cycles. The jacket was water-cooled and the temperature was controlled to ≤40℃. The mixture was then transferred to a vacuum mixer and stirred at -0.095 MPa, 58℃, and 150 rpm for 75 min. After that, curing agent was added and mixed thoroughly. The mixture was then stirred at 2000 rpm for 5 min to obtain a conductive and thermally conductive graphene slurry. After coating, the slurry was pre-cured at 80℃ for 1 h and then cured at 130℃ for 2 h.

[0035] Example 3

[0036] Preparation of component A material: The ionic liquid was preheated to 60°C, graphene was added, and ultrasonic treatment was performed for 40 min. Then, the liquid was cooled to 10°C in an ice-water bath, and flake silver powder and silver-plated copper powder were added in sequence. The mixture was ultrasonically dispersed in an ice-water bath for 40 min to obtain component A material. The mass ratio of graphene, silver powder, silver-plated copper powder, and ionic liquid is 10:8:18:7. The graphene sheet diameter is 30μm and the number of layers is ≤5. The aspect ratio of the sheet-like silver powder is 30:1 and the particle size is 10μm. The particle size of the silver-plated copper powder is 5μm.

[0037] Preparation of component B materials: The ionic liquid was preheated to 60°C, and graphene, multi-walled carbon nanotubes and superconducting carbon black were added in sequence. The mixture was ultrasonically treated for 60 min. The resulting product was transferred to a high-pressure homogenizer, set to 1200 bar, and circulated 5 times. The jacket was water-cooled and the temperature was controlled to ≤35°C to obtain the B component material. The mass ratio of graphene, multi-walled carbon nanotubes, superconducting carbon black, and ionic liquid is 10:7:5:2. The graphene sheet diameter is 3μm and the number of layers is ≤3. The multi-walled carbon nanotubes have a diameter of 20nm and a length of 30μm. The superconducting carbon black has a particle size of 50nm.

[0038] Preparation of component C materials: Add component B to component A while stirring at 2000 rpm. After addition, transfer to a high-pressure homogenizer and cycle at 600 bar for 3 times. Add 20% of the mass of component B as an additive to the product and stir at 1200 rpm for 40 minutes in a mixer to obtain component C.

[0039] Additive preparation: Nitrogen-doped graphene powder was added to deionized water and ultrasonically treated for 15 min to obtain a dispersion. 6% (by weight) aniline was added to the dispersion, and the mixture was magnetically stirred at 300 rpm for 15 min. Then, 0.3% (by weight) carboxylated short-cut multi-walled carbon nanotubes were added, and the mixture was ultrasonically dispersed for 10 min. 5% (by weight) ammonium persulfate solution was added dropwise while maintaining stirring. After the addition was complete, stirring was continued for 30 min. 1 mol / L hydrochloric acid was added to adjust the pH to 3, and stirring was continued for 10 min. The solid was obtained by centrifugation, washed 6 times with deionized water, vacuum dried at 80℃ for 5 h, ground, and sieved through a 300-mesh sieve to obtain the additive. The nitrogen-doped graphene powder has a nitrogen content of 5 at%, ≤4 layers, a sheet diameter of 20 μm, a mass ratio of nitrogen-doped graphene powder to deionized water of 1:50, and an ammonium persulfate solution concentration of 1 mol / L.

[0040] Basic raw material preparation: Prepare materials in the following mass ratios: ionic liquid, E44 type epoxy resin, epoxy diluent AGE, phthalic anhydride, KH560, and PVP K-30.

[0041] Graphene slurry preparation: Epoxy resin, diluent, and coupling agent were added to a mixer and stirred at 200 rpm for 20 minutes. Then, component C, ionic liquid, and dispersant were added, and the mixture was transferred to a high-pressure homogenizer and circulated at 600 bar for 3 cycles. The jacket was water-cooled and the temperature was controlled to ≤40℃. The mixture was then transferred to a vacuum mixer and stirred at -0.095 MPa, 60℃, and 200 rpm for 90 minutes. After that, curing agent was added and mixed thoroughly. The mixture was then stirred at 2000 rpm for 5 minutes to obtain a conductive and thermally conductive graphene slurry. After coating, the slurry was pre-cured at 80℃ for 1 hour and then cured at 130℃ for 2 hours.

[0042] Comparative Example 1: The difference between this comparative example and Example 1 is that no flake silver powder or silver-plated copper powder is added to component A.

[0043] Comparative Example 2 differs from Example 1 in that both Component A and Component B use graphene with a sheet diameter of 10 μm and 5 layers.

[0044] Comparative Example 3 differs from Example 1 in that no additives are added.

[0045] Performance testing: The volume resistivity and thermal conductivity of the graphene slurries prepared in Examples 1-3 and Comparative Examples 1-3 were tested.

[0046] Table 1: Volume Resistivity and Thermal Conductivity Properties Testing items Volume resistivity (Ω·cm) Thermal conductivity (W / (m·K)) Example 1 <![CDATA[2.5×10 -4 ]]> 3.8 Example 2 <![CDATA[2.3×10 -4 ]]> 3.9 Example 3 <![CDATA[2.8×10 -4 ]]> 3.5 Comparative Example 1 <![CDATA[8.6×10 -3 ]]> 2.1 Comparative Example 2 <![CDATA[5.2×10 -3 ]]> 2.6 Comparative Example 3 <![CDATA[3.8×10 -4 ]]> 3.4 In the performance test, the volume resistivity was tested according to GB / T16906-1997 standard. The coating thickness was 0.1 mm. After curing, parallel silver electrodes were prepared on the sample surface with an electrode spacing of 20 mm. The resistance between the two electrodes was measured using a high resistance meter and the volume resistivity was calculated. The thermal conductivity was tested according to GB / T22588-2008 standard. According to the data results, the electrical conductivity and thermal conductivity of the graphene slurry prepared by the method of Examples 1-3 are better than those of Comparative Examples 1-3. Moreover, the data of Examples 1-3 are relatively similar, indicating that the formulation batches are stable and the prepared slurry has both good electrical conductivity and thermal conductivity.

[0047] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0048] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A graphene slurry for electrical and thermal conductivity, characterized in that: It includes component A materials, component B materials, component C materials, and basic raw materials; The raw materials for component A include graphene, silver powder, silver-plated copper powder, and ionic liquid; The graphene sheets in component A have a diameter of 10-30 μm and ≤5 layers; the silver powder is flake-shaped silver powder with a diameter-to-thickness ratio of 30:1 and a particle size of 5-10 μm; and the silver-plated copper powder has a particle size of 3-5 μm. The raw materials for component B include graphene, multi-walled carbon nanotubes, carbon black, and ionic liquids. The graphene sheets in component B have a diameter of 1-3 μm and ≤3 layers, the multi-walled carbon nanotubes have a diameter of 10-20 nm and a length of 10-30 μm, and the carbon black is superconducting carbon black with a particle size of 30-50 nm. The C component material is prepared by mixing the A component material and the B component material, wherein the mass ratio of the total mass of the raw materials of the A component material to the total mass of the raw materials of the B component material is 1.7-2.1:1; The basic raw materials include ionic liquids, epoxy resins, diluents, curing agents, coupling agents, and dispersants. The epoxy resin used in the basic raw materials is E44 type epoxy resin, the diluent is epoxy diluent AGE, the curing agent is phthalic anhydride, the coupling agent is KH560, and the dispersant is PVP K-30.

2. The conductive and thermally conductive graphene slurry according to claim 1, characterized in that, The A component material is prepared by the following method: the ionic liquid is preheated to 55-60℃, graphene is added to the preheated ionic liquid, and ultrasonic treatment is performed for 30-40 minutes. Then, the temperature is lowered to 4-10℃ in an ice-water bath, and silver powder and silver-plated copper powder are added in sequence. The mixture is ultrasonically dispersed in an ice-water bath for 30-40 minutes to obtain the A component material.

3. The conductive and thermally conductive graphene slurry according to claim 1, characterized in that, The B component material is prepared by the following method: the ionic liquid is preheated to 55-60℃, graphene, multi-walled carbon nanotubes and carbon black are added sequentially to the preheated ionic liquid, and the mixture is ultrasonically treated for 50-60 minutes. The resulting product is then transferred to a high-pressure homogenizer, set to 800-1200 bar, and cyclically repeated 5 times. The temperature is controlled at ≤35℃ by jacket water cooling to obtain the B component material.

4. The conductive and thermally conductive graphene slurry according to claim 1, characterized in that, The C component material is prepared by the following method: the B component material is added to the A component material, and the stirring is maintained at 1000-2000 rpm during the addition process. After the addition is completed, the product is transferred to a high-pressure homogenizer and circulated 3 times at 500-600 bar. 20% of the mass of the B component material is added to the product as an additive, and the mixture is stirred at 800-1200 rpm for 20-40 minutes in a mixer to obtain the C component material.

5. The conductive and thermally conductive graphene slurry according to claim 4, characterized in that, The additive is prepared by the following method: nitrogen-doped graphene powder is added to deionized water and ultrasonically treated for 10-15 min to obtain a dispersion. Aniline is added to the dispersion, and the mixture is magnetically stirred at 200-300 rpm for 10-15 min. Then, carboxylated short-cut multi-walled carbon nanotubes are added and ultrasonically dispersed for 5-10 min. Ammonium persulfate solution is added dropwise while maintaining stirring. After the addition is complete, stirring is continued for 30 min. 1 mol / L hydrochloric acid is added to adjust the pH to 2-3, and stirring is continued for 5-10 min. The resulting product is centrifuged to obtain a solid. The solid is washed 4-6 times with deionized water and then vacuum dried at 60-80℃ for 4-5 h. The solid is then ground and sieved through a 300-mesh sieve to obtain the additive.

6. The conductive and thermally conductive graphene slurry according to claim 1, characterized in that, The mass ratio of each raw material in component A is 10:7-8:17-18:6-7.

7. The conductive and thermally conductive graphene slurry according to claim 1, characterized in that, The mass ratio of each raw material in component B is 10:6-7:4-5:1.5-2.

8. The conductive and thermally conductive graphene slurry according to claim 1, characterized in that, The mass ratio of each raw material in the basic raw material is 10:18:1.5-1.8:4-4.5:0.2-0.3:0.6-0.8, and the mass ratio of the C component material to the basic raw material is 1.8-2.1:

1.

9. The conductive and thermally conductive graphene slurry according to claim 5, characterized in that, The nitrogen-doped graphene powder has a nitrogen content of 3-5 at%, ≤4 layers, and a sheet diameter of 20 μm. The mass ratio of the nitrogen-doped graphene powder to deionized water is 1:

50. The mass of aniline is 4-6% of the mass of the dispersion. The mass of carboxylated short-cut multi-walled carbon nanotubes is 0.2-0.3% of the mass of the dispersion. The mass of ammonium persulfate solution is 3-5% of the mass of the dispersion. The concentration of the ammonium persulfate solution is 1 mol / L.

10. The method for preparing the conductive and thermally conductive graphene slurry according to any one of claims 1-9, characterized in that, The process includes the following steps: epoxy resin, diluent, and coupling agent are added to a mixer and stirred at 100-200 rpm for 10-20 minutes. Then, component C, ionic liquid, and dispersant are added, and the mixture is transferred to a high-pressure homogenizer. The homogenizer is set to 500-600 bar and circulated 3 times. The jacket is water-cooled and the temperature is controlled to ≤40℃. Then, the mixture is transferred to a vacuum mixer and stirred at -0.095 MPa, 55-60℃, and 100-200 rpm for 60-90 minutes. Finally, the curing agent is added and mixed thoroughly. The mixture is then stirred at 2000 rpm for 5 minutes to obtain a graphene slurry for electrical and thermal conductivity.